Gender gap in peer-to-peer lending: Evidence from China - Chen, Xiao; Huang, Bihong; Ye, Dezhu (Journal of Banking & Finance, 2020)
This paper documents and analyzes the gender gap in the online credit market. Using data from Renrendai, a leading peer-to-peer lending platform in China, we show that lending to female borrowers is associated with better loan performance, including a lower probability of default, a higher expected profit, and a lower expected loss than for their male peers. However, despite the higher creditworthiness, we don't find any measurable gender impact on funding success rate, meaning that female borrowers have to compensate lenders by providing higher profitability to achieve a similar funding probability. These evidences indicate the existence of a gender gap that discriminate against female borrowers. Further analysis implies that this gender gap is independent of the amount of information disclosed by borrowers.